Security investment, hacking, and information sharing between firms and between hackers - Kjell Hausken (Games, 2017)
A four period game between two firms and two hackers is analyzed. The firms first defend and the hackers thereafter attack and share information. Each hacker seeks financial gain, beneficial information exchange, and reputation gain. The two hackers' attacks and the firms' defenses are inverse U-shaped in each other. A hacker shifts from attack to information sharing when attack is costly or the firm's defense is cheap. The two hackers share information, but a second more disadvantaged hacker receives less information, and mixed motives may exist between information sharing and own reputation gain. The second hacker's attack is deterred by the first hacker's reputation gain. Increasing information sharing effectiveness causes firms to substitute from defense to information sharing, which also increases in the firms' unit defense cost, decreases in each firm's unit cost of own information leakage, and increases in the unit benefit of joint leakage. Increasing interdependence between firms causes more information sharing between hackers caused by larger aggregate attacks, which firms should be conscious about. We consider three corner solutions. First and second, the firms deter disadvantaged hackers. When the second hacker is deterred, the first hacker does not share information. Third, the first hacker shares a maximum amount of information when certain conditions are met. Policy and managerial implications are provided for how firms should defend against hackers with various characteristics.
Keywords: 330; information sharing; cyber security; game theory; asset allocation; cyber war; contest success function; security investment; policy